Fabrication of Surlyn ionomer fibers using a novel coextrusion approach and mechanical property characterization. Issue 42 (6th June 2019) - Wang, Xinting; Li, Xiangjie; Grimme, Christian; Olah, Andrew; Baer, Eric; Wnek, Gary E.
ABSTRACT: We report the fabrication of poly (ethylene‐co‐methacrylic acid) sodium‐neutralized ionomer (Surlyn 8940) fibers via a forced‐assembly coextrusion and layer multiplication process with polystyrene (PS) as the matrix material. The PS separating materials were removed by toluene extraction to yield independent Surlyn fibers. The tensile properties of Surlyn fiber strands were studied under different strain rates. Surlyn fibers were oriented to 300% strain at different temperatures to study the effect of orientation on the tensile properties. The oriented Surlyn fibers were annealed after orientation to further enhance the mechanical properties. Further drawing of these oriented fiber mats to a draw ratio of 4 at 60 °C followed by annealing at 60 °C can afford moduli in excess of 350 MPa and tensile strengths in excess of 70 MPa. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48046. Abstract :